Relasi Virtual Guru Dan Murid Di Ruang Digital: Studi Atas Laman Website Tarekat Syadziliyah dan Naqsyabandi Haqqani - Hanif, Abdulloh (Refleksi Jurnal Filsafat dan Pemikiran Islam, 2024)
Sufis believe that closeness to God cannot be learned alone through intellectual contemplation, but must be experienced through the guidance of a teacher (murshid). The relationship between a murshid and a salik, which they call a suhbah, is described as a friendly relationship that needs to be established in a friendly atmosphere. So with the spirit of such relationships, it is not surprising that Sufism is now being looked at as a solution to the problems of the contemporary social world. Two large Sufism orders, Naqshbandi Haqqani and Shadziliyah, are examples of orders that have successfully gained popularity. His courage in adapting elements of modernity is also one reason why he is increasingly accepted. This congregation not only allows music and dancing in various traditional celebrations, but also builds virtual spaces and provides online bay'at (initiation) services. This phenomenon then raises at least two questions that want to be addressed in this research: 1) how can digital space bridge tarekat practices, and 2) to what extent can the relationship between murshid and murid be established through digital space? This research is entirely qualitative, based on observations of two websites, sufilive.com (for the Naqsyabandi Haqqani congregation) and suficommunities.org (for the Shadziliyah congregation), as well as reading various literature. Apart from that, this research also wants to use Pierre Bourdieu's genetic structuralism approach as an analytical tool. Therefore, this research wants to evaluate the possibility of several vital changes that occur when a relationship that was initially built on the nuances of intimacy with God is mediated by technology. Although it can be considered that this relationship has found a more modern and rational space for manifestation, the transformation of this virtual relationship (suhbah) is important to be explored in depth.